Colorimetric method for determining plant nitrogen - Oliveira, Sebastião A. de (Pesquisa Agropecuaria Brasileira, 2014)
A fairly rapid and precise procedure for colorimetric determination of nitrogen in plant material is described. The effect of the wave length, the influence of reaction time and of pH, the interference of some cations, as well as the optimum concentration interval for nitrogen determination were discussed. The results showed a low coefficient of variation and are in good agreement With those obtained by Kjeldahl digestion and distillation method. It was concluded that the plant nitrogen can be regularly determined by the colorimetric method.